Carbon Aerogels: Synthesis, Modification, and Multifunctional Applications - Liying Li; Guiyu Jin; Jian Shen; Mengyan Guo; Jiacheng Song; Yiming Li; Jian Xiong (Gels)
Amidst global imperatives for sustainable energy and environmental remediation, carbon aerogels (CAs) present a transformative alternative to conventional carbon materials (e.g., activated carbon, carbon fibers), overcoming limitations of disordered pore structures, unmodifiable surface chemistry, and functional inflexibility. This review systematically examines CA-based electrochemical systems as its primary focus, analyzing fundamental charge-storage mechanisms and establishing structure–property–application relationships critical to energy storage performance. We critically assess synthesis methodologies, emphasizing how stage-specific parameters govern structural/functional traits, and detail multifunctional modification strategies (e.g., heteroatom doping, composite engineering) that enhance electrochemical behavior through pore architecture optimization, surface chemistry tuning, and charge-transfer kinetics acceleration. Electrochemical applications are extensively explored, including the following: 1. Energy storage: supercapacitors (dual EDLC/pseudocapacitive mechanisms) and battery hybrids. 2. Electrocatalysis: HER, OER, ORR, and CO2 reduction reaction (CO2RR). 3. Electrochemical processing: capacitive deionization (CDI) and electrosorption. Beyond this core scope, we briefly acknowledge CA versatility in ancillary domains: environmental remediation (heavy metal removal, oil/water separation), flame retardancy, microwave absorption, and CO2 capture.